A non-coding plastid DNA phylogeny of Asian Begonia (Begoniaceae): evidence for morphological homoplasy and sectional polyphyly (2011)
Maximum likelihood and Bayesian analyses of non-coding plastid DNA sequence data based on a broad sampling of all major Asian Begonia sections (ndhA intron, ndhF-rpl32 spacer, rpl32-trnL spacer, 3977 aligned characters, 84 species) were used to reconstruct the phylogeny of Asian Begonia and to test the monophyly of major Asian Begonia sections. Ovary and fruit characters which are crucial in current sectional circumscriptions were mapped on the phylogeny to assess their utility in infrageneric classifications. The results indicate that the strong systematic emphasis placed on single, homoplasious characters such as undivided placenta lamellae (section Reichenheimia) and fleshy pericarps (section Sphenanthera), and the recognition of sections primarily based on a suite of plesiomorphic characters including three-locular ovaries with axillary, bilamellate placentae and dry, dehiscent pericarps (section Diploclinium), has resulted in the circumscription of several polyphyletic sections. Moreover, sections Platycentrum and Petermannia were recovered as paraphyletic. Because of the homoplasy of systematically important characters, current classifications have a certain diagnostic, but only poor predictive value. The presented phylogeny provides for the first time a reasonably resolved and supported phylogenetic framework for Asian Begonia which has the power to inform future taxonomic, biogeographic and evolutionary studies.